Cover Image, Volume 84, Issue 4. Issue 4 (April 2016) - Murray, Brian; Sorci, Mirco; Rosenthal, Joseph; Lippens, Jennifer; Isaacson, David; Das, Payel; Fabris, Daniele; Li, Shaomin; Belfort, Georges
Abstract : The cover image, by Brian Stephen Murray et al., is based on the Research Article A2T and A2V Aβ Peptides Exhibit Different Aggregation Kinetics, Primary Nucleation, Morphology, Structure and LTP Inhibition, DOI:10.1002/prot.24995 .